2000
DOI: 10.1093/intjepid/29.3.579
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of different sources of variation in the antibody responses to specific malaria antigens in children in Papua New Guinea

Abstract: Temporal variation and clustering of immune responses to specific malaria antigens need to be taken into account when planning, conducting and interpreting immuno-epidemiological and vaccine studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
(68 reference statements)
1
4
0
Order By: Relevance
“…This allowed us to examine antibody levels, over time (that is, subsequent antibody response in addition to concurrent responses), within individuals. Our demonstration of the temporal variation in children's antibody levels (figure 1) supports the conclusion of Stirnadel et al [38] that a child's antibody level measured at a single time is not representative of the child's acquired immune response. Therefore, a longitudinal study is a more informative method than are previous crosssectional studies, to examine the relationship between exposure and concurrent, as well as subsequent, antibody development.…”
Section: Discussionsupporting
confidence: 88%
“…This allowed us to examine antibody levels, over time (that is, subsequent antibody response in addition to concurrent responses), within individuals. Our demonstration of the temporal variation in children's antibody levels (figure 1) supports the conclusion of Stirnadel et al [38] that a child's antibody level measured at a single time is not representative of the child's acquired immune response. Therefore, a longitudinal study is a more informative method than are previous crosssectional studies, to examine the relationship between exposure and concurrent, as well as subsequent, antibody development.…”
Section: Discussionsupporting
confidence: 88%
“…Younger girls were found to have P. falciparum parasitemias higher than those in boys in a cross-sectional study of Ghanaian children, but the reverse was true in older age groups [50]. On the other hand, antibody responses to some P. falciparum asexual-stage (non-VSA) antigens were found to be higher in Papua New Guinean girls than in boys, although the statistical significance of this effect was relatively weak and was subsumed by non-sex-related factors [51]. Convincing functional explanations for any of these sex-related effects are lacking, but hormonal changes have been shown to exert strong effects on malaria-related outcomes in older age groups [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…A twin study in Liberia found evidence of heritability in antimalarial antibody responses that did not appear to be determined by HLA class II genes (Sjoberg et al 1992). Familial segregation analysis of immunological responses to malaria antigens in Papua New Guinea has suggested that Mendelian effects might govern specific antigen responses, but the overall picture is complex (Stirnadel et al 1999a(Stirnadel et al , 2000a(Stirnadel et al , 2000b.…”
Section: Family Studiesmentioning
confidence: 99%